Materials for the projected botanical reserves (Kherson region, Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
The results of studies of agricultural landscapes Kherson region – namely provided discovered territories valuable in relation sozological that are steppe enclaves of anthropogenically disturbed areas. Description of designed objects made for the guidelines to the study of protected areas. A conservation to three botanical reserves of local significance, within which represented the remnants of typical fescue-grass steppe. Overall, in three projected objects found 176 species of vascular plants of representatives of 133 families 40 families 3 classes 2 sections. Sozological value are 11 species listed in the list of security at various levels.
Keywords: scientific substantiation, botanical reserves, species composition, sozological value.